Seven-Grooved-Rod, Side-Pumping Concept for Highly Efficient TEM00-Mode Solar Laser Emission through Fresnel Lenses - Costa, Hugo (2023)
Funding Information: The FCT-MCTES fellowship grants 2021.06172.BD, CEECIND/03081/2017, SFRH/BD/145322/2019, PD/BD/142827/2018, and SFRH/BPD/125116/2016 of Hugo Costa, Joana Almeida, Miguel Catela, Dário Garcia, and Cláudia R. Vistas, respectively, are acknowledged. Funding Information: This research was funded by Fundação para a Ciência e a Tecnologia—Ministério da Ciência, Tecnologia e Ensino Superior (FCT—MCTES), grant UIDB/00068/2020. Publisher Copyright: © 2023 by the authors.